PENGARUH MOTIVASI BELAJAR, EFEKTIVITAS PEMBELAJARAN DARING, DAN KECERDASAN EMOSIONAL TERHADAP TINGKAT PEMAHAMAN AKUNTANSI PADA MASA PANDEMI COVID – 19 - Ni Komang Ayu Priantini; Rai Dwi Andayani W (Hita Akuntansi dan Keuangan, 2022)
College level accounting education has the aim of educating students so that these students have good knowledge of accounting so that they can produce competent students as professional accountants, to be able to have adequate academic knowledge and added value, a good understanding of accounting is required. This study aims to determine the effect of learning motivation, effectiveness of online learning, and emotional intelligence on the level of accounting understanding during the covid-19 pandemic. The population in this study includes active students of the Accounting Study Program at the Hindu Indonesia University class 2018-2019 as many as 448 students. The number of samples in this study were 82 people who were determined by calculating the Slovin formula and tested using multiple linear regression analysis techniques. The results of this study indicate that (1) learning motivation has a positive effect on the level of accounting understanding during the covid-19 pandemic. (2) The effectiveness of online learning has a positive effect on the level of accounting understanding during the covid-19 pandemic. (3) Emotional intelligence has a positive effect on the level of accounting understanding during the covid-19 pandemic. In the future, the results of this study can be used as material for consideration in designing regulations and learning methods that can be used to improve the ability and comprehension of students regarding accounting courses.